A method for preparing nano composite low melting point glass insulating coating

By improving the formulation and preparation method of nanocomposite low-melting point glass insulating coating, the peeling problem caused by the difference in thermal expansion coefficient of traditional insulating coatings is solved, and the matching degree of insulation performance and thermal expansion coefficient is improved by modifying the combination of silicon carbide whiskers and oxidized metals.

CN119685824BActive Publication Date: 2025-04-18TIANJIN SHIYU ELECTRONICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510198272.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-22
Publication Date
2025-04-18
Estimated Expiration
2045-02-22

AI Technical Summary

Technical Problem

The difference in thermal expansion coefficient between traditional ceramic insulating materials and metal substrates leads to peeling off the insulating coating and damage to insulation performance. The alkali metal oxides used to adjust the thermal expansion coefficient in low-melting glass trigger ionic conductivity at high temperatures, affecting insulation performance.

Method used

By improving the formulation and preparation method of nanocomposite low-melting glass insulating coating, a specific proportion of zinc oxide, copper oxide, bismuth oxide, boron oxide and modified silicon carbide whiskers are used as components of low-melting glass powders, and the nanocomposite glass insulating coating is formed by ball milling and heat treatment.

Benefits of technology

The thermal expansion coefficient of the nanocomposite low-melting point glass insulating coating is significantly improved, making it closer to the thermal expansion coefficient of the metal matrix, reducing the risk of insulating coating peeling, and improving insulation performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for preparing a nano-composite low-melting-point glass insulating coating, which belongs to the technical field of low-melting-point glass. First, the preparation method comprises the following steps: adding low-melting-point glass powder to pure water by stirring, stirring and ball milling to obtain slurry, coating the slurry on the surface of a metal substrate to obtain a slurry-carrying substrate, and then melting and solidifying the slurry-carrying substrate and then naturally cooling it to room temperature, so as to form a nano-composite low-melting-point glass insulating coating on the surface of the metal substrate. After testing, the thermal expansion coefficient (25°C to 300°C) of the formed glass insulating coating is 13.21×10 ‑6 / ℃~13.74×10 ‑6 / ℃, the difference between the thermal expansion coefficient of the nano-composite low-melting-point glass insulation coating prepared in the present invention and the thermal expansion coefficient of 304 stainless steel is smaller.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of low-melting-point glass, and in particular relates to a method for preparing a nano composite low-melting-point glass insulating coating. Background Art

[0002] With the rapid development of the aviation industry and household appliances, the performance requirements of insulating coatings applied to metal substrates are becoming increasingly stringent. Under a temperature environment of around 400°C, there is a difference in the thermal expansion coefficient between traditional ceramic insulating materials and metal substrates. This mismatch becomes a key factor leading to the peeling of insulating coatings and the loss of insulation performance. Therefore, relevant measures must be taken to regulate the thermal expansion coefficient of the insulating coating so that it can be close to the thermal expansion coefficient of the metal substrate.

[0003] The low-melting-point glass system can just meet this demand, and it has the following advantages: the thermal expansion coefficient of the final glass insulating coating system can be adjusted by changing the raw material composition; the melting point is relatively low, so the preparation temperature of the glass insulating coating system is at a low level, which is extremely beneficial for the metal substrate. However, since the main component used to adjust the thermal expansion coefficient in the low-melting-point glass is alkali metal oxide R2O (where R represents elements such as Na and K), and the migration rate of these alkali metal ions is accelerated under conditions above 250°C, thereby causing ion conductivity, it will have a very serious negative impact on the insulation performance in a high-temperature environment.

[0004] Based on this, it is necessary to improve the formula or preparation method of the glass insulating coating. Relevant improvements have also been made in the prior art. For example, the invention patent with application number 200510041144.2 discloses a preparation method of a nano-composite low-melting-point glass insulating coating. The thermal expansion coefficient of the nano-composite low-melting-point glass insulating coating prepared by the preparation method of the invention is 12.3×10 -6 / ℃ or 11.8×10 -6 / ℃, the softening point is raised from 530℃ to 583℃. The present invention aims to further improve the thermal expansion coefficient of the nano-composite low-melting-point glass insulating coating on the basis of the prior art. Summary of the invention

[0005] The thermal expansion coefficient of the common metal matrix 304 stainless steel in the range of 0℃~300℃ is about 18.4×10 -6 / ℃, while the thermal expansion coefficient of the nanocomposite low-melting-point glass insulating coating prepared in the existing patent is 12.3×10 -6 / ℃ or 11.8×10 -6 / ℃, the difference in thermal expansion coefficient is still large when the nano-composite low-melting-point glass insulating coating prepared in the existing patent is coated on a 304 stainless steel substrate. Therefore, the present invention provides a method for preparing a nano-composite low-melting-point glass insulating coating. The present invention aims to further reduce the difference in thermal expansion coefficient between the nano-composite low-melting-point glass insulating coating prepared by the present invention and the 304 stainless steel substrate by improving the formula and the preparation method.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a nano-composite low-melting-point glass insulating coating comprises the following steps:

[0008] Add low-melting-point glass powder to pure water with stirring, mix and stir for 10 to 20 minutes, and then ball mill for 8 to 12 hours. After the ball milling is completed, a slurry is obtained, and the slurry is coated on the surface of a metal substrate to obtain a slurry-carrying substrate. The slurry-carrying substrate is then heated from room temperature to 300°C at a rate of 5 to 10°C / min, kept warm for 20 to 30 minutes, and then continued to be heated to 1000 to 1100°C at a rate of 5 to 10°C / min, heated at a constant temperature for 1 hour, and then naturally cooled to room temperature, so that a nano-composite low-melting-point glass insulating coating is formed on the surface of the metal substrate.

[0009] Furthermore, the low melting point glass powder is formed by mixing the following components in percentage by mass:

[0010] Zinc oxide 10.64%~18.40%, copper oxide 7.79%~7.87%, bismuth oxide 60.50%~61.15%, boron oxide 11.36%~18.37%, modified silicon carbide whiskers 1.95%~1.97%.

[0011] Furthermore, the low melting point glass powder is formed by mixing the following components in percentage by mass:

[0012] Zinc oxide 13.24%~15.83%, copper oxide 7.82%~7.85%, bismuth oxide 60.72%~60.93%, boron oxide 13.68%~16.02%, modified silicon carbide whiskers 1.95%~1.96%.

[0013] Furthermore, the ball milling medium is a silicon carbide ball milling ball with a diameter of 5 mm, the ball-to-material ratio is 7 to 8:1, and the ball milling speed is 120 to 150 r / min.

[0014] Furthermore, the particle size of the slurry is 20-100 nm.

[0015] Furthermore, the metal substrate is a 2 mm 304 stainless steel sheet.

[0016] Furthermore, the modified silicon carbide whiskers are prepared by the following steps:

[0017] S1. Soak the silicon carbide whisker in a hydrofluoric acid solution with a mass fraction of 10% to 20% for 12 to 24 hours. After soaking, filter and collect the solid component. Wash the solid component with pure water for 3 to 5 times. After washing, obtain acid-treated silicon carbide whiskers. Soak the acid-treated silicon carbide whiskers in a hydrogen peroxide solution with a mass fraction of 30% for 1 to 4 hours. After soaking, filter and obtain hydroxylated silicon carbide whiskers.

[0018] S2. Add phosphoric acid and aluminum hydroxide to pure water with stirring, stir at room temperature for 5 to 10 minutes, then heat up to 75 to 80°C, stir at constant temperature for 5 to 10 minutes, then add hydroxylated silicon carbide whiskers with stirring, after the addition is completed, fill with nitrogen, heat the system to 85 to 90°C, stir at constant temperature for 2 to 5 hours, after the reaction is completed, let it stand and cool to room temperature, filter, collect solid components, and then dry the solid components at a constant temperature of 140 to 150°C to constant weight, and then cool to room temperature to obtain modified silicon carbide whiskers.

[0019] Furthermore, the usage ratio of pure water, phosphoric acid, aluminum hydroxide and hydroxylated silicon carbide whiskers in S2 is 1L:0.3mol:0.1mol:70-100g.

[0020] Beneficial effects of the present invention:

[0021] The present invention provides a method for preparing a nano-composite low-melting-point glass insulating coating. The glass insulating coating is finally formed on the surface of a 2 mm thick 304 stainless steel sheet substrate after grinding, coating and melting and solidifying the self-made low-melting-point glass powder of the present invention. According to the test, the thermal expansion coefficient (25°C to 300°C) of the formed glass insulating coating is 13.21×10 -6 / ℃~13.74×10 -6 / ℃, the glass transition temperature is 317.2℃~368.4℃, and the glass softening temperature is 350.8℃~401.4℃. According to GB / T 20878-2007 "Stainless Steel and Heat-resistant Steel Grades and Chemical Composition", the thermal expansion coefficient of 304 stainless steel in the range of 25℃~100℃ is about 17.2×10 -6 / ℃; the thermal expansion coefficient of 304 stainless steel in the range of 0℃~300℃ is about 18.4×10 -6 / ℃, the difference between the thermal expansion coefficient of the nano-composite low-melting-point glass insulation coating prepared in the present invention and the thermal expansion coefficient of 304 stainless steel is smaller. The specific principle is as follows:

[0022] The self-made low-melting-point glass powder of the present invention is prepared by mixing zinc oxide, copper oxide, bismuth oxide, boron oxide and modified silicon carbide whiskers in a specific mass ratio, wherein zinc oxide itself has a thermal expansion characteristic, in a glass system, zinc oxide will expand as the temperature rises, and zinc oxide can play the role of a network modifier in the glass structure, the expansion of zinc oxide will drive the surrounding glass network structure to expand together, so that the thermal expansion coefficient of the entire glass powder increases; copper oxide is a network modifier, the addition of copper oxide can reduce the order of the glass powder, when the temperature rises, the glass powder with a relatively loose structure is more likely to undergo thermal expansion; the thermal expansion coefficient of bismuth oxide itself is relatively high, and in the glass structure, bismuth oxide can change the distribution and bonding state of oxygen ions in the glass network, providing a larger space and degree of freedom for thermal expansion; in the case of containing a network modifier (copper oxide in the present invention), the network constructed by boron oxide will be partially destroyed, so that the overall structure of the glass becomes loose, and when heated, the glass with such a loose structure will have a larger thermal expansion coefficient; the preparation process of the modified silicon carbide whisker includes acid treatment, hydroxylation treatment and loading of aluminum dihydrogen phosphate The process includes the following steps: after hydrofluoric acid is used to treat the silicon carbide whiskers with acid, the surface of the silicon carbide whiskers is etched, which makes the surface of the silicon carbide whiskers rough. Compared with the smooth whisker surface, the rough surface increases the contact area between the two after mixing with the glass powder. During the thermal expansion process, due to the large contact area, the interaction between the whiskers and the glass matrix is ​​wider, and the whiskers have a greater restriction or synergistic effect on the thermal expansion of the glass matrix, which easily leads to the glass matrix being more inclined to expand freely, thereby increasing the overall thermal expansion coefficient. After the hydroxylation treatment, the surface of the silicon carbide whiskers is Hydroxylation introduces a large number of hydroxyl (-OH) functional groups. The presence of hydroxyl groups changes the surface properties of silicon carbide whiskers from being relatively hydrophobic to being more hydrophilic, which enhances the wettability and compatibility of silicon carbide whiskers with the components in the glass powder during the preparation process, allowing the silicon carbide whiskers to be more evenly dispersed in the glass powder. This uniform dispersion makes the effect of silicon carbide whiskers on various parts of the glass powder more consistent during thermal expansion, and there will be no situation where expansion is inhibited due to local silicon carbide whisker agglomeration, which is conducive to the thermal expansion of the glass as a whole according to its own high expansion trend;After the modified silicon carbide whiskers loaded with aluminum dihydrogen phosphate are ground with water and coated on the metal substrate, the aluminum dihydrogen phosphate can generate AlPO4 and gas when calcined at high temperature. First, AlPO4 has a specific crystal structure. In the glass powder, the presence of crystals will affect the overall structure of the glass. When the temperature rises, the difference in thermal expansion coefficient between the crystal and the glass matrix will cause stress concentration at the interface between the two, thereby increasing the thermal expansion coefficient of the glass powder. Then, the generation and diffusion of gas will form pores and defects inside the slurry during the process of transforming it into a glass insulating coating. These pores and defects will form gas in the glass powder. When the slurry expands due to heat, it provides additional space for the glass insulating coating to expand more freely, resulting in an increase in the thermal expansion coefficient. Finally, aluminum dihydrogen phosphate itself contains phosphate groups, which will complex with metal ions on the surface of the metal substrate and other metal ions in the slurry, thereby improving the bonding performance between the nano-composite low-melting-point glass insulating coating and the metal substrate. In addition, AlPO4, as a high-temperature binder, further improves the bonding performance between the low-melting-point glass insulating coating and the surface of the metal substrate, which helps to reduce the probability of the insulating coating peeling off. ; DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] Preparation of modified silicon carbide whiskers:

[0026] S1, soaking the silicon carbide whisker in a 10% by mass hydrofluoric acid solution for 12 hours, filtering after soaking, collecting the solid component, washing the solid component with pure water for 3 times, and obtaining acid-treated silicon carbide whiskers after washing, soaking the acid-treated silicon carbide whiskers in a 30% by mass hydrogen peroxide solution for 1 hour, and filtering after soaking to obtain hydroxylated silicon carbide whiskers;

[0027] S2. Add 0.3 mol of phosphoric acid and 0.1 mol of aluminum hydroxide to 1 L of pure water with stirring, stir at room temperature for 5 min, then heat to 75 ° C, stir at constant temperature for 5 min, and then add 70 g of hydroxylated silicon carbide whisker with stirring. After the addition is completed, fill with nitrogen protection, heat the system to 85 ° C, stir and react at constant temperature for 2 h. After the reaction is completed, let it stand and cool to room temperature. After filtering, collect the solid components, and then dry the solid components at a constant temperature of 140 ° C to constant weight, and then cool to room temperature to obtain modified silicon carbide whiskers.

[0028] Example 2

[0029] Preparation of modified silicon carbide whiskers:

[0030] S1, soaking the silicon carbide whisker in a hydrofluoric acid solution with a mass fraction of 15% for 24 hours, filtering after soaking, collecting the solid component, washing the solid component with pure water for 5 times, and obtaining acid-treated silicon carbide whiskers after washing, soaking the acid-treated silicon carbide whiskers in a hydrogen peroxide solution with a mass fraction of 30% for 4 hours, and filtering after soaking to obtain hydroxylated silicon carbide whiskers;

[0031] S2. Add 0.3 mol of phosphoric acid and 0.1 mol of aluminum hydroxide to 1 L of pure water with stirring, stir at room temperature for 10 min, then heat to 78 ° C, stir at constant temperature for 10 min, and then stir and add 80 g of hydroxylated silicon carbide whisker. After the addition is completed, fill with nitrogen protection, heat the system to 90 ° C, stir and react at constant temperature for 5 hours. After the reaction is completed, let it stand and cool to room temperature. After filtering, collect the solid components, and then dry the solid components at a constant temperature of 145 ° C to constant weight, and then cool to room temperature to obtain modified silicon carbide whiskers.

[0032] Example 3

[0033] Preparation of modified silicon carbide whiskers:

[0034] S1, soaking the silicon carbide whisker in a 20% by mass hydrofluoric acid solution for 24 hours, filtering after soaking, collecting the solid component, washing the solid component with pure water for 5 times, after washing, obtaining acid-treated silicon carbide whiskers, soaking the acid-treated silicon carbide whiskers in a 30% by mass hydrogen peroxide solution for 4 hours, after soaking, filtering, obtaining hydroxylated silicon carbide whiskers;

[0035] S2. Add 0.3 mol of phosphoric acid and 0.1 mol of aluminum hydroxide to 1 L of pure water with stirring, stir at room temperature for 10 min, then heat to 80 ° C, stir at constant temperature for 10 min, and then add 100 g of hydroxylated silicon carbide whisker with stirring. After the addition is completed, fill with nitrogen protection, heat the system to 90 ° C, stir and react at constant temperature for 5 hours. After the reaction is completed, let it stand and cool to room temperature. After filtering, collect the solid components, and then dry the solid components at a constant temperature of 150 ° C to constant weight, and then cool to room temperature to obtain modified silicon carbide whiskers.

[0036] Example 4

[0037] Preparation of nanocomposite low melting point glass insulating coating:

[0038] First, the low melting point glass powder is mixed with the following mass percentage components:

[0039] Zinc oxide 10.64%, copper oxide 7.87%, bismuth oxide 61.15%, boron oxide 18.37%, and modified silicon carbide whiskers prepared in Example 1 1.97%.

[0040] Then, low-melting-point glass powder was added to pure water with stirring, mixed and stirred for 10 minutes, and then ball milled for 8 hours, wherein the ball milling medium was a silicon carbide ball with a diameter of 5 mm, the ball-to-material ratio was 7:1, and the ball mill speed was 120 r / min. After the ball milling was completed, a slurry (particle size of 50-100 nm) was obtained, and the slurry was coated on the surface of a metal substrate (2 mm 304 stainless steel sheet) to obtain a slurry-carrying substrate, and then the slurry-carrying substrate was heated from room temperature to 300°C at a rate of 10°C / min, kept warm for 20 minutes, and then continued to heat to 1000°C at a rate of 10°C / min, heated at a constant temperature for 1 hour, and then naturally cooled to room temperature, that is, a nano-composite low-melting-point glass insulating coating was formed on the surface of the metal substrate. The thermal expansion coefficient (25°C-300°C) of the prepared nano-composite low-melting-point glass insulating coating was detected by a thermal expansion coefficient meter (DIL 402C, NETZSCH, Germany) was 13.21×10 -6 / ℃, the glass transition temperature is 368.4℃, and the glass softening temperature is 401.4℃. According to GB / T 20878-2007 "Stainless Steel and Heat-resistant Steel Grades and Chemical Composition", the thermal expansion coefficient of 304 stainless steel in the range of 25℃~100℃ is about 17.2×10 -6 / ℃; the thermal expansion coefficient of 304 stainless steel in the range of 0℃~300℃ is about 18.4×10 -6 / ℃. Compared with the 12.3×10 -6 / ℃ and 11.8×10 -6 / ℃, the difference between the thermal expansion coefficient of the nano-composite low melting point (glass transition softening temperature is 401.4℃) glass insulation coating prepared in this embodiment and the thermal expansion coefficient of 304 stainless steel is smaller.

[0041] Example 5

[0042] Preparation of nanocomposite low melting point glass insulating coating:

[0043] First, the low melting point glass powder is mixed with the following mass percentage components:

[0044] Zinc oxide 13.24%, copper oxide 7.85%, bismuth oxide 60.93%, boron oxide 16.02%, and modified silicon carbide whiskers prepared in Example 2 1.96%.

[0045] Then, low-melting-point glass powder was added to pure water with stirring, mixed and stirred for 15 minutes, and then ball milled for 10 hours, wherein the ball milling medium was a silicon carbide ball milling ball with a diameter of 5 mm, the ball-to-material ratio was 7:1, and the ball mill speed was 140 r / min. After the ball milling was completed, a slurry (particle size was 40-70 nm) was obtained, and the slurry was coated on the surface of a metal substrate (2 mm 304 stainless steel sheet) to obtain a slurry-carrying substrate, and then the slurry-carrying substrate was heated from room temperature to 300°C at a rate of 5°C / min, kept warm for 30 minutes, and then continued to be heated to 1050°C at a rate of 5°C / min, heated at a constant temperature for 1 hour, and then naturally cooled to room temperature, that is, a nano-composite low-melting-point glass insulating coating was formed on the surface of the metal substrate. The thermal expansion coefficient (25°C-300°C) of the prepared nano-composite low-melting-point glass insulating coating was detected by a thermal expansion coefficient instrument (DIL 402C, NETZSCH, Germany) was 13.70×10 -6 / ℃, the glass transition temperature is 320.1℃, and the glass softening temperature is 354.5℃. According to GB / T 20878-2007 "Stainless Steel and Heat-resistant Steel Grades and Chemical Composition", the thermal expansion coefficient of 304 stainless steel in the range of 25℃~100℃ is about 17.2×10 -6 / ℃; the thermal expansion coefficient of 304 stainless steel in the range of 0℃~300℃ is about 18.4×10 -6 / ℃. Compared with the 12.3×10 -6 / ℃ and 11.8×10 -6 / ℃, the difference between the thermal expansion coefficient of the nano-composite low melting point (glass transition softening temperature is 354.5℃) glass insulation coating prepared in this embodiment and the thermal expansion coefficient of 304 stainless steel is smaller.

[0046] Example 6

[0047] Preparation of nanocomposite low melting point glass insulating coating:

[0048] First, the low melting point glass powder is mixed with the following mass percentage components:

[0049] Zinc oxide 15.83%, copper oxide 7.82%, bismuth oxide 60.72%, boron oxide 13.68%, and modified silicon carbide whiskers prepared in Example 2 1.95%.

[0050] Then, low-melting-point glass powder was added to pure water with stirring, mixed and stirred for 20 minutes, and then ball milled for 12 hours, wherein the ball milling medium was a silicon carbide ball milling ball with a diameter of 5 mm, the ball-to-material ratio was 8:1, and the ball mill speed was 150 r / min. After the ball milling was completed, a slurry (particle size was 20-50 nm) was obtained, and the slurry was coated on the surface of a metal substrate (2 mm 304 stainless steel sheet) to obtain a slurry-carrying substrate, and then the slurry-carrying substrate was heated from room temperature to 300°C at a rate of 5°C / min, kept warm for 30 minutes, and then continued to heat to 1100°C at a rate of 5°C / min, heated at a constant temperature for 1 hour, and then naturally cooled to room temperature, that is, a nano-composite low-melting-point glass insulating coating was formed on the surface of the metal substrate. The thermal expansion coefficient (25°C-300°C) of the prepared nano-composite low-melting-point glass insulating coating was detected by a thermal expansion coefficient meter (DIL 402C, NETZSCH, Germany) was 13.74×10 -6 / ℃, the glass transition temperature is 317.2℃, and the glass softening temperature is 350.8℃. According to GB / T 20878-2007 "Stainless Steel and Heat-resistant Steel Grades and Chemical Composition", the thermal expansion coefficient of 304 stainless steel in the range of 25℃~100℃ is about 17.2×10 -6 / ℃; the thermal expansion coefficient of 304 stainless steel in the range of 0℃~300℃ is about 18.4×10 -6 / ℃. Compared with the 12.3×10 -6 / ℃ and 11.8×10 -6 / ℃, the difference between the thermal expansion coefficient of the nano-composite low melting point (glass softening temperature is 350.8℃) glass insulation coating prepared in this embodiment and the thermal expansion coefficient of 304 stainless steel is smaller.

[0051] Example 7

[0052] Preparation of nanocomposite low melting point glass insulating coating:

[0053] First, the low melting point glass powder is mixed with the following mass percentage components:

[0054] Zinc oxide 18.40%, copper oxide 7.79%, bismuth oxide 60.50%, boron oxide 11.36%, and modified silicon carbide whiskers prepared in Example 3 1.95%.

[0055] Then, low-melting-point glass powder was added to pure water with stirring, mixed and stirred for 20 minutes, and then ball milled for 12 hours, wherein the ball milling medium was a silicon carbide ball milling ball with a diameter of 5 mm, the ball-to-material ratio was 8:1, and the ball mill speed was 120 r / min. After the ball milling was completed, a slurry (particle size was 30-70 nm) was obtained, and the slurry was coated on the surface of a metal substrate (2 mm 304 stainless steel sheet) to obtain a slurry-carrying substrate, and then the slurry-carrying substrate was heated from room temperature to 300°C at a rate of 5°C / min, kept warm for 20 minutes, and then continued to heat to 1000°C at a rate of 5°C / min, heated at a constant temperature for 1 hour, and then naturally cooled to room temperature, that is, a nano-composite low-melting-point glass insulating coating was formed on the surface of the metal substrate. The thermal expansion coefficient (25°C-300°C) of the prepared nano-composite low-melting-point glass insulating coating was detected by a thermal expansion coefficient meter (DIL 402C, NETZSCH, Germany) was 13.62×10 -6 / ℃, the glass transition temperature is 332.0℃, and the glass softening temperature is 367.1℃. According to GB / T 20878-2007 "Stainless Steel and Heat-resistant Steel Grades and Chemical Composition", the thermal expansion coefficient of 304 stainless steel in the range of 25℃~100℃ is about 17.2×10 -6 / ℃; the thermal expansion coefficient of 304 stainless steel in the range of 0℃~300℃ is about 18.4×10 -6 / ℃. Compared with the 12.3×10 -6 / ℃ and 11.8×10 -6 / ℃, the difference between the thermal expansion coefficient of the nano-composite low melting point (glass transition softening temperature is 367.1℃) glass insulation coating prepared in this embodiment and the thermal expansion coefficient of 304 stainless steel is smaller.

[0056] Comparative Example 1

[0057] Comparative Example 1 is the control group of Example 6, in which 1.95% of the modified silicon carbide whiskers prepared in Example 2 of the raw material in Example 6 are replaced with 1.95% of silicon carbide whiskers, and the remaining raw materials, raw material amounts and preparation methods are consistent with those in Example 6. Finally, a nano-composite low-melting-point glass insulating coating is formed on the surface of the metal substrate. The thermal expansion coefficient (25°C to 300°C) of the prepared nano-composite low-melting-point glass insulating coating is 12.51×10 -6 / ℃, the glass transition temperature is 408.4℃, and the glass softening temperature is 435.0℃. According to GB / T20878-2007 "Stainless Steel and Heat-resistant Steel Grades and Chemical Composition", the thermal expansion coefficient of 304 stainless steel in the range of 25℃~100℃ is about 17.2×10 -6 / ℃; the thermal expansion coefficient of 304 stainless steel in the range of 0℃~300℃ is about 18.4×10 -6 / ℃. Compared with the 12.3×10 -6 / ℃ and 11.8×10 -6 / ℃, the difference between the thermal expansion coefficient of the nano-composite low melting point (glass softening temperature is 435.0℃) glass insulation coating prepared in this comparative example and the thermal expansion coefficient of 304 stainless steel is smaller.

[0058] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.

[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a nano-composite low-melting-point glass insulating coating, characterized in that: The following steps are involved: Add low-melting-point glass powder to pure water with stirring, mix and stir for 10 to 20 minutes, and then ball mill for 8 to 12 hours. After the ball milling is completed, a slurry is obtained, and the slurry is coated on the surface of a metal substrate to obtain a slurry-carrying substrate. The slurry-carrying substrate is heated from room temperature to 300° C. at a rate of 5 to 10° C. / min, kept warm for 20 to 30 minutes, and then continued to be heated to 1000 to 1100° C. at a rate of 5 to 10° C. / min, heated at a constant temperature for 1 hour, and then naturally cooled to room temperature, so as to form a nano-composite low-melting-point glass insulating coating on the surface of the metal substrate; The low-melting glass powder is mixed by the following components in percentage by mass: 10.64% to 18.40% zinc oxide, 7.79% to 7.87% copper oxide, 60.50% to 61.15% bismuth oxide, 11.36% to 18.37% boron oxide, and 1.95% to 1.97% modified silicon carbide whiskers; The modified silicon carbide whisker is prepared by the following steps: S1. Soak the silicon carbide whisker in a hydrofluoric acid solution with a mass fraction of 10% to 20% for 12 to 24 hours. After soaking, filter and collect the solid component. Wash the solid component with pure water for 3 to 5 times. After washing, obtain acid-treated silicon carbide whiskers. Soak the acid-treated silicon carbide whiskers in a hydrogen peroxide solution with a mass fraction of 30% for 1 to 4 hours. After soaking, filter and obtain hydroxylated silicon carbide whiskers. S2. Add phosphoric acid and aluminum hydroxide to pure water with stirring, stir at room temperature for 5 to 10 minutes, then heat up to 75 to 80°C, stir at constant temperature for 5 to 10 minutes, then add hydroxylated silicon carbide whiskers with stirring, after the addition is completed, fill with nitrogen, heat the system to 85 to 90°C again, stir at constant temperature for 2 to 5 hours, after the reaction is completed, let it stand and cool to room temperature, filter, collect solid components, and then dry the solid components to constant weight at a constant temperature of 140 to 150°C, and then cool to room temperature to obtain modified silicon carbide whiskers.

2. The method for preparing a nano-composite low-melting-point glass insulating coating according to claim 1, characterized in that: The low-melting-point glass powder is mixed by the following components in percentage by mass: 13.24% to 15.83% zinc oxide, 7.82% to 7.85% copper oxide, 60.72% to 60.93% bismuth oxide, 13.68% to 16.02% boron oxide, and 1.95% to 1.96% modified silicon carbide whiskers.

3. The method for preparing a nano-composite low-melting-point glass insulating coating according to claim 1, characterized in that: The ball milling medium is a silicon carbide ball milling ball with a diameter of 5 mm, the ball-to-material ratio is 7 to 8:1, and the ball milling speed is 120 to 150 r / min.

4. The method for preparing a nano-composite low-melting-point glass insulating coating according to claim 1, characterized in that: The particle size of the slurry is 20-100 nm.

5. The method for preparing a nano-composite low-melting-point glass insulating coating according to claim 1, characterized in that: The metal substrate is a 2 mm 304 stainless steel sheet.

6. The method for preparing a nano-composite low-melting-point glass insulating coating according to claim 1, characterized in that: The usage ratio of pure water, phosphoric acid, aluminum hydroxide and hydroxylated silicon carbide whiskers in S2 is 1L:0.3mol:0.1mol:70-100g.

Citation Information

Patent Citations

  • Method for preparing nano composite low melting point glass insulation coating

    CN1899999A

  • Slurry for preparation of glass fluorescent layer used for LED encapsulation

    CN102730974A

  • Copper-clad plate not prone to creepage and tracking and preparation technology of copper-clad plate

    CN115923267A